Pengaruh Daya Tarik Wisata Terhadap Minat Kunjung Wisatawan Di Masjid Abdul Kadim Epil - Ayu Andira; Achmad Syarifuddin; Hasril Atieq Pohan (ScidacPlus, 2023)
In this study, researchers tppk the title The Effect of Tourist Attraction on Tourist Visit Interests at the Abdul Kadim Epil Mosque. The purpose of this study was to determine whether there is influence of the attractiveneess of the mosque one the interest in visiting tours. This type of research uses decriptive quantitative research with the variabel tourist attraction as (X) and the variabel interest in visiting tourist as (Y). The sampling technique is by means of probability sampling, with a total sample of 100 respondents. Data collection was obtained using a questionnaire that had been tested using validity and reability tests, as well as to test the feasibility of variabel using simple linear regression. While the data was tested by t test (partial test and R2(R Square) with the help of the SPSS version 25.0 program. The regression result equation is Y=1.010+0.39X, which mean that the attractiveness variabel has a significant effect on tourist interest. The R2 value is 0.852 meaning the variable of interest in visiting can be explained by the attractiveness of 85.2% meanwhile, 14.8% is explained by other variables not examined in this study such as promotions, services, support services and others. Based on the t test it is known that tcount(23.788)>ttable (1.98447), with a significance level of 0.000<0.05 then H0 is rejected and accepts Ha, meaning that the independent variabel (attraction) partially affects the dependent variable (intention to visit).